Tolerance of peritoneal and residual renal function to intraperitoneal gadolinium‐based agents: An animal experimental study of magnetic resonance peritoneography. Issue 3 (22nd November 2021) - Dong, Jing; Li, Wenlu; Shu, Jian; Lv, Cheng; Gan, Linwang; Bai, Jiao
Abstract: Background: MR (Magnetic resonance) peritoneography is sensible for continuous ambulatory peritoneal dialysis (CAPD)‐related complications, which could offer excellent soft‐tissue contrast and allows a multiplanar imaging evaluation of complications. However, there is no study about the optimal concentration of the gadolinium‐based agents nor the side effects of gadolinium‐based agents on peritoneum and residual renal function. Method: Five different groups of uremic rats and two groups of normal rats were injected with a 40‐ml mixture of peritoneal dialysate and gadolinium‐based agents at varying concentrations prior to MR peritoneography. Thereafter, MR image obtained was evaluated by two experienced radiologists blinded to the concentrations. Peritoneal morphology and thickness of the uremic rats were also assessed using hematoxylin and eosin and Masson staining. Residual renal function was evaluated using serum creatinine levels and hematoxylin and eosin (HE) staining of pathological kidney sections. Results and Conclusion: The gadolinium‐based agents used in this experiment have no significant effect on residual renal function. There is no obvious difference in the image quality at the different gadolinium‐based agents concentration. Due to the adverse effects of gadolinium‐based agents in the previous studies, we suggest reducing the dose of gadolinium‐based agents during MR peritoneography to the lowest limits.